Minnaert Resonance in an Array of Two-Dimensional Bubbles - Vargas-Hernandez, y (American Physical Society, 2023)
Transmission and reflection of sound across a dense layer of long rectangular quasi-two-dimensional bubbles in a polymeric matrix are measured over two frequency ranges, 150-260 and 670-1130 kHz. Contrary to what is expected, considering the high acoustic impedance contrast between air and the matrix, there is high transmission across the layer, especially in the lower-frequency range. These results are explained by a monopolar Minnaert-like resonance of bubbles, which radiates sound in both directions of the bubble layer. The Minnaert resonance is computed for two-dimensional bubbles, revealing a resonance frequency within the lowest-frequency range used. The transmission and reflection coefficients are theoretically computed by considering the bubble array as a homogeneous layer with a resonant acoustic impedance. © 2023 American Physical Society.